2022
DOI: 10.3390/molecules27196191
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Synthesis of Silver Nanoparticles Using Catharanthus roseus and Its Cytotoxicity Effect on Vero Cell Lines

Abstract: Background: Type 2 diabetes mellitus (DM2) is a chronic and sometimes fatal condition which affects people all over the world. Nanotherapeutics have shown tremendous potential to combat chronic diseases—including DM2—as they enhance the overall impact of drugs on biological systems. Greenly synthesized silver nanoparticles (AgNPs) from Catharanthus roseus methanolic extract (C. AgNPs) were examined primarily for their cytotoxic and antidiabetic effects. Methods: Characterization of C. AgNPs was performed by UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Together, the biogenic AgNPs’ high negative charge revealed that these nanoparticles were negatively charged all over their surface in aqueous solutions, highlighting their high colloidal dispersivity and long-term stability. 43 The presence of bioactive compounds in H. sabdariffa flower extract, which was demonstrated by FTIR analysis, may be the cause of the noticed negative charge of the biogenic AgNPs, confirming their ability to repel each other, and highlighting their stability and uniform distribution condition in water. 44
Figure 10 Zeta potential analysis of the biogenic AgNPs.
…”
Section: Resultsmentioning
confidence: 86%
“…Together, the biogenic AgNPs’ high negative charge revealed that these nanoparticles were negatively charged all over their surface in aqueous solutions, highlighting their high colloidal dispersivity and long-term stability. 43 The presence of bioactive compounds in H. sabdariffa flower extract, which was demonstrated by FTIR analysis, may be the cause of the noticed negative charge of the biogenic AgNPs, confirming their ability to repel each other, and highlighting their stability and uniform distribution condition in water. 44
Figure 10 Zeta potential analysis of the biogenic AgNPs.
…”
Section: Resultsmentioning
confidence: 86%
“…The ZnO-NPs' inherent ability to disrupt the machinery that makes proteins and to cause tiny gaps in bacterial cell walls may be the cause of their bactericidal effect [53,55].…”
Section: Discussionmentioning
confidence: 99%
“…If the IC 50 is between 20 and 89 µ g/mL, the extract is classified as moderately cytotoxic. If the IC 50 is <20 µ g/mL, the extract is classified as cytotoxic [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%